Architectural Design Decision Documentation through Reuse of Design Patterns - Durdik, Zoya (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2016)
The ADMD3 approach presented in this book enchances the architectural design documentation of decision via reuse of design patterns. It combines the support for evaluation of pattern application, semi-automated documentation of decision rationale and trace links. The approach is based on a new kind of design pattern catalogue, whereby usual pattern descriptions are captured together with question annotations to the patterns and information on architectural structure of patterns.